The importance of intake: a gut feeling - Gerritsen, Karin G. (Ann Transl Med, 2015)
Limiting enteric sodium absorption is an attractive option when renal sodium excretion is disturbed. An effective approach in the gut appears to be inhibition of the electroneutral Na(+)/H(+) exchangers (NHE), in particular NHE3. Recently, fluid retention, blood pressure and target organ injury were limited in rats with cardiorenal syndrome when treated with the NHE3 inhibitor tenapanor. The downside was that the osmotic fecal load leads to watery feces. Tenapanor also induced marked reductions in enteric phosphorus absorption in rats with cardiorenal syndrome on a high phosphorus intake and resulted in marked reductions in renal injury and practically prevented vascular calcification. We have yet to discover the clinical relevance in volume terms and vascular calcifications in patients in relation to the tolerated dose. However, even if the tenapanor-induced reduction in sodium adsorption is limited in humins, combination of tenapanor therapy with diuretics may be an interesting option in selected patients.